Extremely Rare Isolated Small‐Intestinal Polyp Diagnosed by Double‐Balloon Endoscopy in an Asymptomatic Adult Patient - Kentaro Tominaga; Annenkov Alexey; Yuto Tanaka; Osamu Shibata; Yuichi Kojima; Yuzo Kawata; Nao Nakajima; Kazuya Takahashi; Hiroki Sato; Satoshi Ikarashi; Kazunao Hayashi; Ken‐ichi Mizuno; et al. (Clinical Case Reports)
ABSTRACT We present the first reported case of an isolated small‐bowel intestinal juvenile polyp in an adult. This case is particularly noteworthy as it was asymptomatic, detected via computed tomography, localized by capsule endoscopy, and successfully resected via double‐balloon endoscopy before the development of acute symptoms.